H‐ferritin and CD68+/H‐ferritin+ monocytes/macrophages are increased in the skin of adult‐onset Still's disease patients and correlate with the multi‐visceral involvement of the disease. (28th July 2016) - Ruscitti, P.; Cipriani, P.; Ciccia, F.; Di Benedetto, P.; Liakouli, V.; Berardicurti, O.; Carubbi, F.; Guggino, G.; Di Bartolomeo, S.; Triolo, G.; Giacomelli, R.
Summary: Adult‐onset Still's disease (AOSD) patients may show an evanescent salmon‐pink erythema appearing during febrile attacks and reducing without fever. Some patients may experience this eruption for many weeks. During AOSD, exceptionally high serum levels of ferritin may be observed; it is an iron storage protein composed of 24 subunits, heavy (H) subunits and light (L) subunits. The ferritin enriched in L subunits (L‐ferritin) and the ferritin enriched in H subunits (H‐ferritin) may be observed in different tissues. In this work, we aimed to investigate the skin expression of both H‐and L‐ferritin and the number of macrophages expressing these molecules from AOSD patients with persistent cutaneous lesions. We observed an increased expression of H‐ferritin in the skin, associated with an infiltrate in the biopsies obtained from persistent cutaneous lesions of AOSD patients. Furthermore, a positive correlation between H‐ferritin skin levels as well as the number of CD68 + /H‐ferritin + cells and the multi‐visceral involvement of the disease was observed. Our data showed an increased expression of H‐ferritin in the skin of AOSD patients, associated with a strong infiltrate of CD68 + /H‐ferritin + cells. Furthermore, a correlation between the levels of H‐ferritin as well as of the number of CD68 + /H‐ferritin + cells and the multi‐visceral involvement of the disease was observed.